PENDAMPINGAN BELAJAR DI DESA PADANG CERMIN KECAMATAN SELESAI KABUPATEN LANGKAT - Nudia Yultisa; Tri Indah Rezeki; Nurul Utami (Universitas Islam Sumatear Utara, 2022)
Community Service in 2021 will be carried out in Padang Cermin Village, Finish District, Langkat Regency. In this community service program, we carry out many work programs, one of which is mentoring learning for children in Pasar II Hamlet, Padang Cermin Village. Learning mentoring activities through tutoring are the process of providing assistance or assistance to individuals or groups by one or more supervisors who have expertise in the field in making choices, , adjustments and solving learning problems related to changes in behavior as a result of experience, training or education. Stimulation. Learning assistance through tutoring activities can improve through appropriate group guidance services. To increase student motivation in addition to learning guidance to motivate, it is necessary to have mental guidance by providing positive motivation. Giving rewards seems to make a good contribution. Rewards given are not always in the form of goods but can be in the form of praise or positive consequences. Tutoring institutions outside of school are an alternative for students to get material that has not been taught in school. The decision to include children in courses or tutoring institutions is the right decision for children. There they can gain knowledge that was not taught by teachers at school. However, not all children can take lessons or tutoring. This happened in the children's neighborhood in Pasar II Hamlet, Padang Cermin Village, Finished Subdistrict, which was far from the urban center and because of the high cost of tutoring. By seeing these obstacles, it makes the lecturers and students of STKIP Budidaya Binjai feel called to do service in the area. This community service activity is a means of conveying the usefulness of knowledge and a sense of concern for lecturers and students towards the community in the field of education in the form of assistance through tutoring activities at home or at the post. The purpose of this activity is to improve academic achievement and student motivation.